Educational Technology Undergraduates’ Performance in a Distance Learning Course Using Three Courseware Formats - Falode, Oluwole Caleb; Mohammed, Ibrahim Abba (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
Most educators’ inability to provide learning contents that suit different learning styles has caused a lot of problems in terms of performance. Thus, to cater to students’ preferences in terms of access to learning contents, the distance learning regulatory body in Nigeria emphasized that course materials should be developed in mixed-media formats. This study was carried out to compare the effects of printed, video, and Moodle-based courseware on educational technology students’ achievement, retention, and satisfaction in a distance learning course. A quasi-experimental design was employed for the study involving 108 participants from three experimental groups. The learning content and instruments, subjected to validation and reliability tests, where values of 0.78 and 0.86 were obtained using the Pearson product moment correlation and Cronbach’s alpha for achievement and satisfaction inventory, respectively, were administered within a four-week period. Data collected were analyzed using descriptive and inferential statistics. Findings indicated that the printed, video, and Moodle-based courseware formats improved students’ achievement with mean gain scores of 47.92, 40.89, and 43.03, respectively. A significant difference was observed in the achievement (F (2,104) = 8.67, p < 0.05), retention (F (2,104) = 29.406, p < 0.05), and satisfaction scores (F (2,104) = 5.662, p < 0.05) of the three groups. Open and distance learning administrators in Nigeria are recommended to produce and deploy printed, video, and Moodle-based formats of courseware to meet different students’ learning preferences.